Fluorescent materials for monitoring mitochondrial biology - Chu, Yeojeong; Park, Jisoo; Kim, Eunha; Lee, Sanghee (Materials, 2021)
Mitochondria play important roles in diverse cellular processes such as energy production, cellular metabolism, and apoptosis to promote cell death. To investigate mitochondria-associated biological processes such as structure, dynamics, morphological change, metabolism, and mitophagy, there exists a continuous demand for visualizing and monitoring techniques elucidating mitochondrial biology and disease-relevancy. Due to the advantages of high sensitivity and practicality, fluorescence phenomena have been most widely used as scientific techniques for the visualization of biological phenomena and systems. In this review, we briefly overview the different types of fluorescent materials such as chemical probes, peptide-or protein-based probes, and nanomaterials for monitoring mitochondrial biology.
Keywords: Biological phenomena; Biological process; Cellular metabolism; Continuous demand; Energy productions; Fluorescent materials; Monitoring techniques; Morphological changes; Fluorescence imaging; Fluorescent chemical probes; Fluorescent nanosensors; Mitochondria; Mitochondria-targeting peptides